Stretching and its effects on recovery: A review - Sands, W. A.; McNeal, J. R.; Murray, S.; Ramsey, M. W.; Sato, K.; Mizuguchi, S.; Stone, M. H. (Strength and Conditioning Journal, 2013)
Stretching is a commonly prescribed exercise activity that has been applied to warm-up, increasing range of motion (ROM), and recovery from training. The practitioner should understand the effects of stretching exercise and the inherent differences between types of stretching exercises and activities designed to enhance 'looseness' and freedom of motion. Stretching to enhance ROM may be contraindicated when applied to recovery activities. Stretching for recovery should be pain-free motion within the constraints of maximum rom of a joint. For a video abstract of this article, see supplemental digital content 1 (see video, http://links.lww.com/scj/a119).